2020
DOI: 10.1101/2020.08.23.20180281
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiologically most successful SARS-CoV-2 variant: concurrent mutations in RNA-dependent RNA polymerase and spike protein

Abstract: The D614G mutation of the Spike protein is thought to be relevant for SARS-CoV-2 infection. Here we report biological and epidemiological aspects of this mutation. Using pseudotyped lentivectors, we were able to confirm that the G614 variant of the Spike protein is markedly more infectious than the ancestral D614 variant. We demonstrate by molecular modelling that the replacement of aspartate by glycine in position 614 facilitates the transition towards an open state of the Spike protein. To understand whether… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
27
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 31 publications
(49 reference statements)
10
27
0
4
Order By: Relevance
“…Only seven countries were included in this analysis -Saudi Arabia, Oman, UAE, Bahrain, Palestine, Morocco, and Jordan, where none of the variants was significantly correlated with an increase in CFR ( Figure 5). Consistent with previous studies [22,23], we confirm that NSP12_P323L seems to have quickly co-evolved following S_D614G…”
Section: Resultssupporting
confidence: 92%
“…Only seven countries were included in this analysis -Saudi Arabia, Oman, UAE, Bahrain, Palestine, Morocco, and Jordan, where none of the variants was significantly correlated with an increase in CFR ( Figure 5). Consistent with previous studies [22,23], we confirm that NSP12_P323L seems to have quickly co-evolved following S_D614G…”
Section: Resultssupporting
confidence: 92%
“…Further, a small but significant positive correlation was reported between the prevalence of S(G614) in a given geographic area and case-fatality rate in that region [ 39 ]. Another group observed a similar trend, although not statistically significant in their dataset [ 40 ]. Moreover, computational models of evolutionary dynamics suggest that D614G is under strong selective pressure [ 31 ].…”
Section: Introductionmentioning
confidence: 59%
“…Further, quantitative estimates of the basic reproductive number R 0 from infection incidence data suggest that viruses bearing S(G614) are 31% more transmissible than D614, although this analysis did not consider the effect of concomitant changes at other loci in the circulating viral strains [ 41 ]. Various studies have identified co-segregation of changes in other viral genes along with the D614G mutation in spike, such as the P323L mutation in the viral polymerase RdRp which may attenuate replication to compensate for the increased transmissibility of D614G viruses [ 40 , 42 , 43 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Many papers suggested that D614G mutation in the viral spike (S) protein SARS-CoV-2 can influence the ability of virus transmission. In recent work [1], it was shown D614G influences the rate of disease transmission only in combination with the P323L mutation in the viral polymerase. We have sequenced 28 full genomes of SARS-CoV-2, obtained from clinical material from patients of different ages.…”
mentioning
confidence: 99%
“…По данным всемирной базе GISAID, мутация D614G в S-белке встречается в 76,53% последовательностей (по данным на 20 августа 2020); первый полногеномный сиквенс, в котором она была зарегистрирована -hCoV-19/England/NORW-E82AE/2020 [3]. В недавней работе [1]…”
unclassified